Performance of silixol on crop productivity and soil health enhancement in black gram (Vigna mungo L.) for sustainable agriculture - Palanisamy, Murali Arthanari; Sakila, M; Anitha, K. G.; Paul, R. Arockia Infant; Sathya Priya, R.; Jagathjothi, N.; Yuvaraj, M.; Panneerselvam, P.; Sharmila, R. (Informa UK Limited, 2025)
The decline in black gram yield was primarily linked to rainfed crops, poor nutrient management, inadequate assimilate partitioning, flower dropping, poor pod setting, and physiological issues. Fertilizers with foliar spray at the reproductive stage in pulse could aid it by directly delivering the nutrients to the site of food synthesis, resulting in a faster food supply and improved crop performance. The trials were conducted to assess the efficacy of silixol on black gram growth and yield as well as soil health. Treatments including 50% RDF combined with vermicompost (VC), silixol granules soil application (SA), and silixol foliar spray (FS) are examined in the RCBD with three replications. Results revealed that 50% RDF + VC at 2.5 t/ha + silixol granules (SA) at 20 kg/ha + silixol (FS) at 1% on 40 DAS showed significant improvement in plant height (67.5 cm), DMP (1959 kg/ha), LAI (2.24), chlorophyll content (94.95 SPAD value) on 60 DAS, root nodules (667 Nos/plant) and grain yield (849 kg/ha) with 61% increase over RDF alone. Similarly, an increase in the soil microbial biomass carbon, dehydrogenase activity, and microbial population by 16.0%, 59.6% and 31.8%, respectively were by applying silixol granules with foliar spray in combination with integrated fertilization over control.